Ginsenoside Compound K Enhances Fracture Healing via Promoting Osteogenesis and Angiogenesis - Ding, Lingli; Gu, Song; Zhou, Bingyu; Wang, Min; Zhang, Yage; Wu, Siluo; Zou, Hong; Zhao, Guoping; Gao, Zhao; Xu, Liangliang (Frontiers in Pharmacology, 2022)
Fractures have an extraordinarily negative impact on an individual's quality of life and functional status, particularly delayed or non-union fractures. Osteogenesis and angiogenesis are closely related to bone growth and regeneration, and bone modeling and remodeling. Recently Chinese medicine has been extensively studied to promote osteogenic differentiation in MSCs. Studies have found that Ginseng can be used as an alternative for tissue regeneration and engineering. Ginseng is a commonly used herbal medicine in clinical practice, and one of its components, Ginsenoside Compound K (CK), has received much attention. Evidence indicates that CK has health-promoting effects in inflammation, atherosclerosis, diabetics, aging, etc. But relatively little is known about its effect on bone regeneration and the underlying cellular and molecular mechanisms. In this study, CK was found to promote osteogenic differentiation of rat mesenchymal stem cells (MSCs) by RT-PCR and Alizarin Red S staining in vitro. Mechanistically, we found CK could promote osteogenesis through activating Wnt/β-catenin signaling pathway by immunofluorescence staining and luciferase reporter assay. And we also showed that the tube formation capacity of human umbilical vein endothelial cells (HUVECs) was increased by CK. Furthermore, using the rat open femoral fracture model, we found that CK could improve fracture repair as demonstrated by Micro-CT, biomechanical and histology staining analysis. The formation of H type vessel in the fracture callus was also increased by CK. These findings provide a scientific basis for treating fractures with CK, which may expand its application in clinical practice.